SWOT Analysis of Sharia Mudharabah Savings Marketing Strategy in Increasing the Number of Customers at BMT NU East Java, Purwoharjo Branch - Muhammad Kanzul Fikri; Siti Nur Afifatul Hikmah; Lukluk Martiana (PT FORMOSA CENDEKIA GLOBAL, 2022)
The research focuses on Mudharabah Savings Sharia Marketing Strategies in Increasing the Number of Customers at BMT NU East Java Purwoharjo Branch and SWOT Analysis of Mudharabah Savings Sharia Marketing Strategies in Increasing the Number of Customers at BMT NU East Java Purwoharjo Branch. Researchers use a qualitative approach to the type of case study. qualitative approach to describe and analyze phenomena, events, social activities, attitudes, beliefs, thoughts of people individually and in groups. Based on the results of research conducted by researchers, it was found that the results of the marketing strategy prioritized consumer orientation by providing the highest satisfaction and focusing on the appearance of institutions in serving consumers. Planning that is carried out actively and well will be able to anticipate future developments, even factors outside the business environment will be mastered or predicted in advance.